A turning point for planning theory? Overcoming dividing discourses - Judith Innes (University of California, Institute of Urban and Regional Development (IURD), 2013)
After communicative planning theory (CPT) emerged in the 1980's, challenging assumptions and prevailing theories of planning, debates ensued among planning theorists that led to apparently opposing groups with little space for mutual learning. The most difficult obstacle is that critiques of CPT framed several dichotomies making different perspectives appear incompatible. This article seeks to advance the dialogue of planning theory perspectives by acknowledging the key tensions embedded in this framing, but arguing that they can be viewed as reflecting contradictions to be embraced as an opportunity for a more robust planning theory. Drawing on Manuel Castells' (2009) theory of communication power the article explores four of these contradictions and shows how in each case embracing the contradictions as aspects of our complex world can lead to insights and a richer planning theory. The article concludes with suggestions for improved dialogue among theorists and identifies research that can advance our understanding of communication power.
Keywords: 330; communicative planning theory; communication power; collaborative rationality; discourse; critique